1996
DOI: 10.1007/bf01690098
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-pseudomonal antibiotics in the emergence ofStenotrophomonas maltophilia in cystic fibrosis patients

Abstract: A retrospective case-control study of 12 patients positive for Stenotrophomonas maltophilia and 24 age-sex-matched controls revealed that in the year prior to initial isolation, colonised patients spent more days in hospital and received more days of oral ciprofloxacin, intravenous anti-pseudomonal antibiotics, and nebulised aminoglycosides. They were also more likely to have grown Pseudomonas aeruginosa at some time in the past, despite there being no difference in current chronic infection with this organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 11 publications
0
52
0
Order By: Relevance
“…Tobramycin was the first antibiotic used for inhalational therapy for CF patients (175). The delivery of antipseudomonal aminoglycoside therapy by nebulizer has been associated with an increased risk for colonization by S. maltophilia (82). The intermittent delivery of aerosolized tobramycin by a nebulizer (cycles of 300 mg tobramycin or taste-masked placebo twice daily for 28 days followed by 28 days without treatment) did not increase the selection of tobramycin-resistant S. maltophilia and resulted in persistent treatment-emergent S. maltophilia in a very low number of patients (43,276).…”
Section: New Treatment Strategiesmentioning
confidence: 99%
“…Tobramycin was the first antibiotic used for inhalational therapy for CF patients (175). The delivery of antipseudomonal aminoglycoside therapy by nebulizer has been associated with an increased risk for colonization by S. maltophilia (82). The intermittent delivery of aerosolized tobramycin by a nebulizer (cycles of 300 mg tobramycin or taste-masked placebo twice daily for 28 days followed by 28 days without treatment) did not increase the selection of tobramycin-resistant S. maltophilia and resulted in persistent treatment-emergent S. maltophilia in a very low number of patients (43,276).…”
Section: New Treatment Strategiesmentioning
confidence: 99%
“…This suggests that the organism resides in the lungs under continuous antibiotic pressure, which raises concerns on the emergence of antibiotic resistance 38 . Several factors contribute to the resistance of P. aeruginosa, including its genetic capacity to express a wide repertoire of resistance mechanisms and its ability to become resistant through mutations in chromosomal genes which regulate resistance genes 39 . Additionally, P. aeruginosa can acquire resistance genes from other organisms via plasmids, transposons and bacteriophages.…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…In a retrospective case-control study, Denton et al found that in the years preceding the first isolation of S. maltophilia, colonized patients had received more oral ciprofloxacin and intravenous anti-pseudomonal antibiotics 39 . Similarly, upon evaluating the effect of intermittent inhalation of tobramycin on the microbiology of respiratory secretions 40 , Burns et al found that the use of oral quinolones was the only factor that significantly increased the risk of S. maltophilia isolation 34 .…”
Section: Clinical Impactmentioning
confidence: 99%
“…It should be noted that the low susceptibility showed by S. maltophilia strains can be considered an important virulence factor in patients under antibiotic treatment. In fact, prior exposure of the patient to antibiotics has been identified as an important risk factor associated with S. maltophilia infection or colonization (9,10).…”
mentioning
confidence: 99%